Membangun Soft Skill dan Hard Skill Siswa SMK pada Era Digital - Beni Junedi; Reihan Mutaqin; Siti Adira Kania; Vani Khusnul Khatimah; Nurul Ainaya Tohariah (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2024)
Education in the digital era demands students to possess comprehensive skills, both in terms of soft skills and hard skills. Motivational seminar activities organized by the Student Field Experience Practicum (PPL) with speakers from field supervising lecturers aim to assist 12th-grade vocational high school students in developing both types of skills. This article discusses the methods, results, and discussions related to the effectiveness of these motivational seminar activities